2020
DOI: 10.3389/fmicb.2020.01855
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest and Postharvest Application of Garlic and Rosemary Essential Oils for Controlling Anthracnose and Quality Assessment of Strawberry Fruit During Cold Storage

Abstract: This study assessed the feasibility of using essential oils (EOs) against Colletotrichum nymphaeae inciting strawberry anthracnose. Two EOs, extracted from Allium sativum (garlic) and Rosmarinus officinalis (rosemary), were selected because their fungicide efficacy was already well characterized under laboratory and greenhouse conditions. We characterized both EOs in terms of efficacy and impact on qualitative traits and sensory quality of strawberry fruit. The gas chromatography-mass spectrometry analysis con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 93 publications
4
24
0
1
Order By: Relevance
“…The surface of the colony was gently scraped, after which the mycelial debris was removed and filtered through three layers of sterile muslin cloth. The concentration of the spore suspension (1 × 10 6 spores/ ml) was adjusted using a haemocytometer ( Hosseini et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The surface of the colony was gently scraped, after which the mycelial debris was removed and filtered through three layers of sterile muslin cloth. The concentration of the spore suspension (1 × 10 6 spores/ ml) was adjusted using a haemocytometer ( Hosseini et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“… DS (%) = (((0 × P 0) + (1 × P 1) + (2 × P 2) + (3 × P 3) + (4 × P 4) + (5 × P 5))/ N × G ) × 100 where P 0 to P 5 is the total number of the evaluated leaves in each corresponding scale, N —total number of leaves, G —number of maximum grades observed in scale [ 42 ]. DR (%) = ( Xc − Xt )/ Xc × 100 where Xt is the mean of DS per treatment, and Xc is the mean of DS in the inoculated control [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, ascorbic acid content is closely related to variety, maturity, and storage conditions, so the determination of ascorbic acid content can be used as the main physiological index of fruit and vegetable preservation. Essential oils also keep strawberries fresh and protect against loss of total phenols, flavonoids, ascorbic acid, and soluble solids (Hosseini et al, 2020). From Figure 8, it was found that the content of ascorbic acid in the tissue infected by CEP2 and CEP5 showed a downward trend.…”
Section: Changes Of Ascorbic Acid Contentmentioning
confidence: 98%